Assessment of Agricultural Taxes Reform on Sudanas Economy (Global Journal of Science Frontier Research, 2012)
This study evaluates the effects of agricultural taxes changes on Sudan economy. It uses the Computable General Equilibrium model as analytical tool; with Sudan Social Accounting Matrix for year 2004 constitutes the core database. The activity and commodity accounts are disaggregated into agriculture (sesame, sorghum, cotton, wheat and other agriculture), industry and service accounts. The model results show that reduction of wheat import tariff increases wheat imports, output and export of cotton, sesame, industrial and services sectors. The overall effect of this policy is improvement of GDP, balance of trade and investment. The results reveal that reduction of production tax or value added tax for each crop would increase its domestic output and exports and reduce those of the other crops, except for sorghum. The overall effect of reducing these taxes improves the GDP and private consumption despite the mixed effect on investment and balance of trade. The study recommends reduction of taxes on agriculture and increasing direct taxes on private companies to compensate government revenue loss.
Keywords: Sudan; CGE; SAM; Import Tariff; VAT and Production Tax